Literature Review: Personal Hygiene for Patients after Laparotomy - Puji Triyanto; Dwi Retno Sulistyaningsih; Suyanto Suyanto; Dwi Heppy Rochmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Personal hygiene care in post-laparotomy patients is very important to accelerate the healing process and prevent infection. Good hygiene is associated with a reduced risk of post-operative complications. The purpose of this study was to analyze the effect of personal hygiene on the recovery of post-laparotomy patients and the factors that influence it. This study utilized a Systematic Literature Review design, adhering to the PRISMA guidelines. The search for relevant articles was conducted across two primary scientific databases, SINTA and Scopus, covering the publication period from 2020 to 2025. The search strategy was formulated using a combination of keywords: